METAPHORICAL REPRESENTATION OF BEAUTY AND STYLE IN ENGLISH FASHION MAGAZINE TEXTS (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
This article examines the metaphorical representation of beauty and style in English fashion magazine texts from a linguistic perspective. The study focuses on metaphor as a key stylistic device in fashion discourse and explores its role in influencing readers’ perception. Based on the analysis of selected English fashion magazine articles, the research identifies the semantic and pragmatic features of metaphorical expressions related to beauty and style. Furthermore, the study highlights the use of metaphors as persuasive tools in advertising and communicative strategies. The findings contribute to a deeper understanding of linguistic features in fashion discourse.